Prenatally diagnosed fetal heart rhythm abnormalities—incidence, diagnosis and outcome - Jelena Stamenković; Vojislav Parezanović; Olivera Kontić-Vučinić; Ivan Stefanović; Maja Trkulja; Ida Jovanović; Aleksandar Ljubić; Milena Srbinović (Clinical and Experimental Obstetrics & Gynecology)
Backrounds: Fetal arrhythmias represent a significant cause of fetal morbidity and mortality and occur in approximately 1–3% of pregnancies. The unknown fetal arrhythmias are the cause of intrauterine fetal demise in as many as 3–10% of cases, as well as the cause of unexplained fetal hydrops or premature births. Methods: A fetal echocardiography test makes it possible to notice structural heart defects at very early stages of pregnancy. The ultrasound heart rate monitoring also involves the use of specific Doppler methods. Heart rhythm disorders may occur in the form of tachycardia (sinus tachycardia (ST), supraventricular tachycardia (SVT) and atrial flutter (AF)) or in the form of bradycardia (sinus bradycardia (SB), atrial bigeminy (AB) and complete AV block). The most frequently diagnosed fetal heart rhythm disorders are isolated extrasystoles with no clinical significance. Results: In this study, we have examined 7863 fetuses (182 were multiple gestations). Out of the total number of examined patients, 572 fetuses (7.23%) had pathological heart features, while 127 (1.61%) had some form of rhythm disorder. Conclusions: The ability to recognize the heart rhythm disorder and commence the treatment in a timely manner increases the treatment success rate.